Scenario analysis for net zero: The applicability of climate neutrality studies for transitioning firms in the German building sector and energy-intensive industry - Fernanda Ballesteros; Franziska Schütze; Catherine Marchewitz; Alexandra Hüttel (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
Various stakeholders are increasingly encouraging companies from the real economy to adopt measures facilitating their transition towards carbon neutrality. In this context, companies are expected to implement forward-looking strategies and climate-related reporting practices using scenario analysis aligned with scientific evidence and credible pathways to net zero carbon emissions. This paper examines the potential of scenario analysis as an element for transitioning to net zero. We review and compare eight existing economy and sector level climate neutrality studiesfor Germany that were published between 2019 and 2021, analysing their respective applicability as a science-based reference scenario for companies to strengthen strategy development and forward-looking reporting practices. Using the logical framework approach, we assess relevant transition indicators like technologies, energy and resource efficiency, carbon pricing, and other steering instruments for the building and energy-intensive industry sectors. These indicators measure progress towards climate neutrality and could be included as a crucial component in transition plans. We find that, although modelling approaches for the studies differ, they often converge on similar results that can partially be translated to indicators at the firm level and, thereby, may serve as reference scenarios for their transition planning.
Keywords: G32; M41; M48; L52; L61; L85; Q51; Q58; 330; Climate Change; Scenarios Analysis; Decarbonization; Sustainability Reporting; Transition Plans; Sectoral Pathways; Building Sector; Energy-Intensive Industry Sector